Measurement of the charge asymmetry in B±→ϕK± and search for B±→ϕπ± decays - Aaij, Roel; Aquines Gutiérrez, Osvaldo; Bachmann, Sebastian; Bien, Alexander; Blouw, Johan; Britsch, Markward; De Cian, Michel; Di Canto, Angelo; Dordei, Francesca; Färber, Christian; Gersabeck, Evelina; Hansmann-Menzemer, Stephanie; et al. (Physics letters, 2013)
The CP-violating charge asymmetry in B±→ϕK± decays is measured in a sample of pp collisions at 7 TeV centre-of-mass energy, corresponding to an integrated luminosity of 1.0 fb−1 collected by the LHCb experiment. The result is ACP(B±→ϕK±)=0.022±0.021±0.009, where the first uncertainty is statistical and the second systematic. In addition, a search for the B±→ϕπ± decay mode is performed, using the B±→ϕK± decay rate for normalization. An upper limit on the branching fraction B(B±→ϕπ±)<1.5×10−7 is set at 90% confidence level.